(3ebGdI GdEScfOQ GdEaQhOjSi aj GdCVOGO hCfgG ChGFd GdCTjGA Ydi QCi CQSWhWGdjS GdMcjes - (3GdGScfOQ GdGaQhOjSjs
(3ChdgG (B:s
(3bGd GdEScfOQ c Ef GQSWh PcQ ai cJGH GdSeGY GdWHYji Cf LejY GdChdjf CJabhG Ydi Cf GdCVOGO ChGFd GdCTjGA cdgG s
(3BNQgG (B:s
(3hbhdg (B: (3Efg jchf HYVgG ef HYV , hGSJHGf CjVkG eG eYfi bhdg (B: (3Ef GdCVOGO OGFeI HCbGhjd eSJbUGg hGVMI dGeQO dgG JeJ GdebGdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B15s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(798/15) s
Keywords: (3GdadSaI hGdefWbs